Development of an operational excellence framework for organisational performance improvement in the Sudanese aviation industry - Mohamed Ibrahim Osman; Roslina Mohammad; Shari Mohd Yusof; Shreeshivadasan Chelliapan (Journal of Industrial Engineering and Management (JIEM), 2021)
Purpose: The purpose of this study is to investigate the Critical Success Factors (CSFs) for successful implementation of Operational Excellence (OE) by the organisations in the Sudanese aviation industry, as well as to determine the resulted impacts in the improved organisational performance and competitive advantage, and to quantify the benefits. Design/methodology/approach: The Critical Success Factors (CSFs) of OE were provided and dissected to reveal its integrated components and their importance levels. These factors include leadership, people management, continuous improvement, operational strategy, and asset optimisation. Also, the impacts (outcomes) further categorised in the four financial results, quality of products or services, efficiency, and satisfaction groups were presented, while the weight of each outcome was highlighted. Findings: With the OE's conceptual framework, the critical success factors to achieve OE were identified. Hence, from the five main factors, the expert panel members suggested the leadership factor to be the most important to achieve OE in the Sudanese aviation industry. Ranking of the five critical success factors and the forty sub factors provided a better understanding of the Sudan situation, specifically concerning the effective implementation of OE philosophy. Research limitations/implications: The findings of the sub-factors reported in this study were not enough. As a result, the future studies must focus on the detailed descriptions of sub-factors that are related to each of the critical factor identified. Practical implications: Efficiency in the organisations is generated and enhanced when the organisations become efficient in reducing the waste of time, raw materials, unnecessary processing, in addition to the energy used in transportation, storing, and operating plant. Besides, the state of effectiveness is achieved when the organisation achieves its long-term goals through increased customer satisfaction and is able to prove its reason for being. OE is critical as it assures both the efficiency and effectiveness of organisations. Originality/value: The past research activities have relatively over-emphasised in the unilateral "result-driven" perspective of OE that corresponds with the limited concern for enablers, the critical forms and focus of OE. Thus, this issue is a shortcoming that this paper attempts to address.
Keywords: 650; aviation industry; continuous improvement; leadership; Operational excellence; people management; performance improvement